2019
DOI: 10.1002/ppul.24485
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of cardiac function in pediatric patients with mild to moderate bronchial asthma in the era of cardiac strain imaging

Abstract: Objective Bronchial asthma is a common chronic inflammatory airway disease, which may be associated with pulmonary hypertension and cardiac dysfunction. The aim of this study was to evaluate the ability of 2D‐speckle tracking echocardiography (2D‐STE) and tissue doppler imaging (TDI) to detect subtle cardiac dysfunction in pediatric patients with mild to moderate bronchial asthma. Methodology The study included 30 children with mild to moderate bronchial asthma and 27 age‐matched healthy controls. Both groups … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 35 publications
2
6
0
Order By: Relevance
“…We did not find any significant difference between all groups regarding parameters of LV diastolic functions. These findings were in line with previous studies [10,13] .…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…We did not find any significant difference between all groups regarding parameters of LV diastolic functions. These findings were in line with previous studies [10,13] .…”
Section: Discussionsupporting
confidence: 94%
“…Some studies described RV hypertrophy in asthmatic patients [10][11][12] . Another study described RV dilatation rather than hypertrophy [13] . These variations can be explained by the difference in study populations and the fact that we did not include patients with severe asthma in our study.…”
Section: Discussionmentioning
confidence: 99%
“…It can represent the deformation of the local atrial segment without being affected by the load and other negative damages. It has excellent reproducibility and easy parameter measurement so as to provide accurate data for evaluating the contractility of the whole atrium and the segmental contraction in the long-axis direction and quantifying cardiac function [21]. Ijuin et al [22] indicated that the strain peak was more stable and reproducible in the upper atrium, the peak gradually decreased from top to bottom, and the lower part was the same as the baseline, which was consistent with the results of this study.…”
Section: Discussionsupporting
confidence: 90%
“…2D images were acquired in the apical four‐chamber, apical long axis, and apical two‐chamber views for LV longitudinal strain while parasternal short‐axis views at the base, papillary muscles, and apex were used for evaluation of LV circumferential and radial strains. The global longitudinal strain of RV was measured in the apical four chamber view 9,10 . Breath‐holding was not applied due to the young age of most patients who were not cooperative.…”
Section: Methodsmentioning
confidence: 99%